Dari Penertiban Ke Pemberdayaan: Urgensi Pembentukan Peraturan Daerah Tentang Pedagang Kaki Lima - Ishak, Dicky Aldines; Abdussamad, Zamroni; Ahmad (RechtJiva, 2026)
The presence of Street Vendors (PKL) is an important part of the informal economic sector, contributing significantly to the local economy, particularly in providing employment and distributing goods and services to the community. However, the growth of street vendors not accompanied by a comprehensive arrangement system often leads to social, legal, and spatial planning issues, especially in areas that do not yet have specific regulations. This article aims to analyze the urgency of establishing a Regional Regulation on the arrangement and empowerment of Street Vendors in Gorontalo Regency and to examine the ideal scope of regulation thru a Regulatory Impact Assessment (RIA) approach. This research uses a normative legal research method with a legislative, conceptual, and case approach. The research results indicate that the absence of local regulations leads to legal uncertainty, social conflict, and weak protection and empowerment of street vendors. The formation of Regional Regulations has become an urgent need to create orderly, fair, and inclusive street vendor governance. Thru the RIA approach, it was found that the ideal regulation should include aspects of data collection, zoning, simple licensing, economic empowerment, legal protection, and cross-sectoral coordination. This article concludes that the formation of Regional Regulations on Street Vendors is a strategic step in regulating public space without sacrificing the economic sustainability of small communities.